Efeito de exercícios com suspensão e pendulação corporal sobre o torque, eletromiografia, espessura muscular e funcionalidade de indivíduos com lesão medular torácica - Frison, Verônica Baptista (2016)
Background: Traumatic spinal cord injury (TSCI) is a severe, incapacitating, neurological syndrome that leads to changes in sensitivity, motor function, and the autonomic system of body segments located below the level of injury. Although it is one of the most devastating injuries and poses multiple challenges for the patients, family, and clinicians involved, physical therapy can lead to neurological improvements in patients with TSCI. The purpose of this study was to evaluate the effects of corporal suspension and pendulum exercises (CHORDATA® method) on torque, muscle activation, muscle thickness, and functionality in patients with TSCI. Methods: This study was a randomized, controlled clinical trial including 26 male TSCI patients (in whom injury occurred up to 3 years earlier at the thoracic level; age, 18–65 years). The subjects were categorized into two groups: an intervention group (IG; n = 14) and a control group (CG; n = 12). Before and after a rehabilitation program, which comprised 16 sessions of suspension and pendulum exercises (twice/week, 50 minutes/session), we evaluated the following parameters in each subject: maximal voluntary isometric trunk flexion and extension torques; electromyographic activity of the external oblique, rectus abdominis, and longissimus muscles; muscle thickness of the external oblique, internal oblique, transversus abdominis, rectus abdominis, and multifidus muscles; and functionality (adapted reach test). Mean ± standard deviation values were used to summarise continuous data, which were then compared at the baseline using t-tests. Categorical variables were expressed as counts and percentages. Between-group baseline differences were assessed using chi-square or Fisher’s exact tests, as required. Analysis of covariance, with adjustments for baseline measurements, was conducted to evaluate between-group differences after the 16 exercise sessions. The results were presented as mean ± standard deviation with the estimated adjusted difference between groups, followed by 95% confidence intervals. The study significance level was set at α = 0·05. Data were analysed using SPSS version 22.0 (SPSS, Inc., Chicago, USA).This trial is registered with Clinical Trials.gov, #NCT02316067. Findings: The CG and IG patients had similar ages (p = 0·93), injury time (p = 0·41), injury level (p = 0·27), injury mechanism (p = 0·22), American Spinal Injury Association (ASIA) scale (p = 0·11), injury type (p = 0·22), and functional reach (p = 0·11). Post-intervention, the IG trunk flexion (58%, p = 0·004) and extension (76%, p = 0·005) torques were higher in the IG than in the CG. Similar between-group differences were observed post-intervention for RA-L absolute RMS values (p = 0·028), RA-R RMS values normalized to the resting state (p = 0·047), and functional reach (p = 0·015). Muscle thickness for all muscles was higher in the IG patients as compared to the CG patients post-intervention (p < 0·002), except for the MULT-R muscle (p = 0·057). Interpretation: Sixteen sessions of suspension and pendulum exercises improved rectus abdominis muscle activation, trunk muscle structure and strength, and reaching capacity in TSCI patients. Thus, this novel, effective rehabilitation method may improve functionality in TSCI patients.